Quelle image de la ville pour un projet de développement urbain durable ? L’exemple d’Aubervilliers - Hélène Chelzen; Pierre Pech (VertigO)
It is well known that urban pictures are very often used in urban planning and decision-making. The role of pictures as supporting several aims such as political decisions or urban marketing is well documented. Actually, sustainable development is increasingly chosen as a tool for urban planning. Planning, regulations, legislation, certification, economics, policy, social and environmental impact related to sustainable and future cities are more and more important in urban projects. As shown with other uses of pictures, urban landscapes in urban planning has a great place but the actual place of sustainable development public policies increase new using of pictures in which sustainable urban projects are the first level of the argumentation. In France, as in other countries and especially in suburbs of wide towns as Paris, the urban context need new urban project. Suburban communities provide one important part of the urban growing. The aim of this article is to document the example of one specific and old industrial suburban community of Paris, Aubervilliers, whose public policies about urban projects integrate pictures use the sustainable development as an argument. Through this example we examine the place of sustainable development in decision tools of urban management.